CLIMATE CHANGE IN CENTRAL ASIA AND ITS EFFECTS ON THE GREEN ECONOMY - Sanakulov Mukhriddin Sadriddinovich (TADQIQOTLAR.UZ, 2024)
Annotation The article highlights the impact of climate change on Central Asia and its implications for the region’s transition to a green economy. It explains how rising temperatures, glacial melting, water scarcity, and extreme weather events threaten the environment and socio-economic stability. The green economy is presented as a solution, focusing on renewable energy, sustainable agriculture, green infrastructure, and regional cooperation. The article also addresses the challenges of funding, dependence on fossil fuels, and political instability, offering insights into policy innovation and international collaboration. Central Asia is experiencing significant climate change impacts, including rising temperatures, water scarcity, and land degradation, which threaten its environment and economy. This article explores how these challenges influence the region’s shift toward a green economy. It identifies opportunities in renewable energy, sustainable agriculture, and green infrastructure while emphasizing the need for regional cooperation. Despite progress, barriers such as limited funding and fossil fuel reliance persist. By adopting effective policies and leveraging international support, Central Asia can achieve sustainable growth and resilience against climate challenges.